Effects of sterilization conditions and milk protein composition on the rheological and whipping properties of whipping cream. (January 2016) - Long, Zhao; Zhao, Mouming; Sun-Waterhouse, Dongxiao; Lin, Qinlu; Zhao, Qiangzhong
Abstract: This paper investigates the impact of substituting 25% sodium caseinate with whey protein concentrate on the properties of whipping creams subjected to boiling sterilization (100 °C for 30 min), autoclaving (115 °C for 20 min or 121 °C for 15 min), or ultra-high-temperature sterilization (139 °C for 7s). Results showed that the interactions induced by the heat treatments among milk proteins, and among the milk proteins, oil droplets and/or polysaccharides accounted for the changes in physical properties of whipping creams. Higher sterilization intensity led to emulsions with larger droplet sizes and denser network structure, causing higher viscosity and a more solid-like structure. Both partial substitution with whey protein concentrate and an increase of heating intensity influenced the whipping properties of cream negatively, but the former caused less negative effect and could reduce fat coalescence. Graphical abstract: Confocal scanning laser micrographs of whipping creams subjected to different sterilization conditions: (a) NaCN alone system and (b) NaCN/WPC system. Scale bar represents 50 μm. NaCN and WPC refer to sodium caseinate and whey protein concentrate, respectively. Highlights: Heat intensity: 115 °C/20 min >121 °C/15 min >100 °C/30 min >139 °C/7s. Higher heat intensity produced larger droplet size and more solid-like structure. Higher heat intensity reduced the overrun. The addition of WPC promoted the droplet flocculation but reduced oil coalescence. The addition of WPC reduced the overrun but enhanced the foam stability.